THE SYSTEM OF PUBLIC ADMINISTRATION ENTITIES IN THE FIELD OF FORENSIC EXPERT ACTIVITY: CONCEPT, STATUS, POWERS, SUBORDINATION AND COORDINATION (International Journal of Innovative Technologies in Economy, 2023)
Introduction. Quite complex and contradictory transformation processes aimed at constructing a democratic state and its institutions are taking place in Ukraine. Problem Statement. Modernization of public administration in Ukraine, changes in social relations, insufficient effectiveness of forensic expert support of law enforcement activities and the judiciary, the need for organizational and legal transformations in the field of forensic expert activity. Purpose. Consider the system of public administration entities in the field of forensic expert activity, their concepts, status, powers, subordination and coordination of activities Materials and Methods. General scientific and special research methods: analysis, modeling and forecasting, dialectical, structural-functional, synergistic, normative-logical, comparative-legal, analogy, extrapolation and legal interpretation. Results. It is proposed to consider the system of public administration entities in the field of forensic expert activity as a complete, interdependent, hierarchically structured set of subjects who, in accordance with the purpose and within the limits of authority, conduct public administration in the field of forensic expert activity in order to implement their own tasks and functions with the aim of providing justice in Ukraine with an independent, qualified and objective examination, focused on the maximum use of the achievements of science and technology. Conclusions. The system of public administration entities in the field of forensic expert activity consists of: 1) ministries and other state bodies, to the sphere of management of which belong state specialized institutions that conduct forensic expert activity; 2) entities of forensic expert activity. The creation of a system of self-governance of forensic experts will contribute to the reduction of state regulation in the field of forensic examination and must be approved by law. In the normative legal acts on advisory and other auxiliary bodies, in particular, in the Regulation on the Coordinating Council on Forensic Examination Issues under the Ministry of Justice of Ukraine, the sections on the formation of the composition should take into account the right of forensic experts who are not employees of state specialized institutions and members of public organizations of forensic experts, to be elected to advisory and other auxiliary bodies. The creation of an effective system of public administration subjects in the field of forensic expert activity should be based on the European administrative and legal concept of “public administration”, developed relevant theoretical provisions, and have an appropriate legal basis. It is necessary to establish new approaches to the system of public administration entities in the field of forensic expert activity in order to ensure justice with independent, qualified and objective examination that would meet the requirements of international standards and modern challenges.